Safeguarding history : trailblazing adventures inside the worlds of collecting and forging history - Rendell, Kenneth W. (Whitman Publishing, LLC, 2023)
Safeguarding Trailblazing Adventures Inside the Worlds of Collecting and Forging History, with foreword by Doris Kearns Goodwin, is the eloquent, captivating, moving, and complex story of the world’s most prominent dealer in historical documents, letters, manuscripts, and artifacts. Kenneth Rendell has traveled the world, tracking down, buying, and selling the most significant, iconic historical letters and documents from the Renaissance to the present day. Safeguarding History chronicles his adventures.